Eight unexpected cases of vancomycin associated acute kidney injury with contemporary dosing. Issue 5 (May 2017) - O'Donnell, J. Nicholas; Ghossein, Cybele; Rhodes, Nathaniel J.; Peng, Jessica; Lertharakul, Tina; Pham, C. Kim; Scheetz, Marc H.
Abstract: Vancomycin is one of the most commonly utilized antibiotics in US hospitals. It remains the drug of choice for the treatment of serious infections caused by methicillin-resistant Staphylococcus aureus . For many of these deep-seated infections, guidelines recommend achieving troughs of 15–20 mg/L for treatment efficacy. At our institution we observed a number of cases of presumed vancomycin-induced acute tubular necrosis clinically diagnosed by the nephrology service. We report eight cases of presumed vancomycin-induced acute tubular necrosis, three of which required hemodialysis before resolution of nephrotoxicity. Only three of the eight patients received nephrotoxins prior to development of nephrotoxicity. All eight patients ultimately recovered renal function following discontinuation.